GENEALOGI DAN PRODUK PEMBAHARUAN HUKUM WARIS TURKI - arif sugitanata; Suud Sarim Karimullah; Wifa Lutfiani Tsani (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
This article discusses genealogy and products of inheritance law renewal in Turkiye. The focus of this research is genealogically how inheritance law was born in Turkiye and what are the products of inheritance law reform in Turkiye. In this study, researchers used literature studies whose data sources came from related books and journals. This study concludes that the geneology of inheritance law renewal in Turkiye broadly began when the Turkiye state was founded and led by Mustofa Kemal as the first leader, where Ankara was the capital. This had an impact on the Turkiye country which carried out many major reforms influenced by the West, such as the prohibition of polygamy, giving freedom to women and upholding equality for them, including in the field of inheritance, where men and women get one to one. Then the inheritance law products imposed by the Turkiye state were included in the Turkish Civil Code. The amendment was approved by the Turkiye National Assembly on November 27, 2001 and socialized through the Turkiye Daily Newspaper on December 8, 2001. The amendment contains 1030 articles, one of which relates to inheritance law in Turkiye, where inheritance distribution is enforced in the Turkiye inheritance law regulations only applies to nuclear families who can receive inheritance. Meanwhile, relatives outside the nuclear family cannot become heirs unless the nuclear relatives also take care of the heirs, so that they receive a share of the inheritance. Then in inheritance law there is no difference between the rights, position and degrees of men and women because both are considered the same, so there is no difference in obtaining a share of the inheritance.